turboTDDFT 2.0—Hybrid functionals and new algorithms within time-dependent density-functional perturbation theory - Ge, Xiaochuan; Binnie, Simon J.; Rocca, Dario; Gebauer, Ralph; Baroni, Stefano (Computer physics communications, 2014)
We present a new release of the turboTDDFT  code featuring an implementation of hybrid functionals, a recently introduced pseudo-Hermitian variant of the Liouville–Lanczos approach to time-dependent density-functional perturbation theory, and a newly developed Davidson-like algorithm to compute selected interior eigenvalues/vectors of the Liouvillian super-operator. Our implementation is thoroughly validated against benchmark calculations performed on the cyanin (C21O11H21) molecule using the Gaussian 09 and turboTDDFT  1.0 codes. Program title: turboTDDFT 2.0 Catalogue identifier: AEIX_v2_0 Program summary URL:http://cpc.cs.qub.ac.uk/summaries/AEIX_v2_0.html Program obtainable from: CPC Program Library, Queen’s University, Belfast, N. Ireland Licensing provisions: GNU General Public License, version 2 No. of lines in distributed program, including test data, etc.: 5995995 No. of bytes in distributed program, including test data, etc.: 122184812 Distribution format: tar.gz Programming language: Fortran 95, MPI. Computer: Any computer architecture. Operating system: GNU/Linux, AIX, IRIX, Mac OS X, and other UNIX-like OS’s. Classification: 16.2, 16.6, 7.7. External routines: turboTDDFT 2.0 is a tightly integrated component of the Quantum ESPRESSO distribution and requires the standard libraries linked by it: BLAS, LAPACK, FFTW, MPI. Does the new version supercede the previous version?: Yes Nature of problem: Calculation of the optical absorption spectra of molecular systems. Solution method: Electronic excited states are addressed by linearized time-dependent density-functional theory within the plane-wave pseudo-potential method. The dynamical polarizability can be computed in terms of the resolvent of the Liouvillian super-operator, using a pseudo-Hermitian variant of the Lanczos recursion scheme. As an alternative, individual eigenvalues of the Liouvillian can be computed via a newly introduced variant of the Davidson method. In both cases, hybrid functionals can now be used. Reasons for new version: To implement new features. Summary of revisions: New features implemented: 1.Hybrid functionals.2.Pseudo-Hermitian Lanczos recursion algorithm.3.All-new Davidson-like solver for the Liouvillian eigenvalue equation (“Casida equation”). Restrictions: Spin-restricted formalism. Linear-response regime. Adiabatic XC kernels only. Hybrid functionals are only accessible using norm-conserving pseudo-potentials. Unusual features: No virtual orbitals are used, nor even calculated. Within the Lanczos method a single recursion gives access to the whole optical spectrum; when computing individual excitations using the Davidson method, interior eigenvalues can be easily targeted. Additional comments: !!! The distribution file for this program is over 121 Mbytes and therefore is not delivered directly when download or E-mail is requested. Instead a html file giving details of how the program can be obtained is sent. Running time: From a few minutes for small molecules on serial machines up to many hours on multiple processors for complex nanosystems with hundreds of atoms.